The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0100-84042006000100009
|View full text |Cite
|
Sign up to set email alerts
|

Tolerância ao congelamento de sementes de pau-brasil (Caesalpinia echinata Lam.) influenciada pelo teor de água inicial

Abstract: -(Freezing tolerance in seeds of Caesalpinia echinata Lam. (brazilwood) as influenced by the initial water content). Caesalpinia echinata Lam., a Brazilian tropical woody species, is at risk of extinction due to the economic exploitation of its heartwood. In natural environment, under warm temperatures, seeds of C. echinata germinate immediately after shedding, keeping their viability under storage only up to three months after harvesting. These seeds are tolerant to desiccation (until 7.6% wet basis) maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 6 publications
2
19
0
13
Order By: Relevance
“…The seeds of C. echinata presented germination percentage lower than that of other analyzed species. However, Hellmann et al (2006) have reported higher values for the seeds harvested from the same plantation of C. echinata. Therefore, the differences found could be attributed to the seasonal differences in environmental conditions rather than to genetic factors.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The seeds of C. echinata presented germination percentage lower than that of other analyzed species. However, Hellmann et al (2006) have reported higher values for the seeds harvested from the same plantation of C. echinata. Therefore, the differences found could be attributed to the seasonal differences in environmental conditions rather than to genetic factors.…”
Section: Discussionmentioning
confidence: 92%
“…(Caesalpinioideae) are also tolerant to desiccation (Barbedo et al, 2002). However, these seeds loose their viability within three months when stored under the laboratory conditions and maintain high germinability under sub-zero conditions up to two years (Hellmann et al, 2006). The seeds of Inga vera Will.…”
Section: Introductionmentioning
confidence: 99%
“…(pau-brasil) toleram a dessecação e mantêm a viabilidade por até 18 meses quando armazenadas com 0,1 g H 2 O g -1 MS sob baixas temperaturas (7-8 °C), perdendo a capacidade germinativa em 30 dias, quando armazenadas em temperatura ambiente, ao redor de 25 °C (Barbedo et al 2002). Essas sementes também toleram o congelamento quando armazenadas com aquele teor de água, produzindo alta porcentagem de plântulas normais após 24 meses de armazenamento (Hellmann et al 2006). Os principais compostos de reserva dessas sementes são proteínas (8%-10%), lipídios (ca.…”
Section: Sementes Maduras De Caesalpinia Echinataunclassified
“…Proteínas específicas e ROs são sintetizados e acumulados de forma tardia durante o desenvolvimento de sementes e aparentemente também estão envolvidos com a tolerância à dessecação e com a longevidade de sementes ortodoxas (Bernal-Lugo & Leopold 1992, Lin & Huang 1994, Castro et al 2004. No entanto, sementes de pau-brasil, consideradas ortodoxas e tolerantes à dessecação (Barbedo et al 2002), mantiveram alta viabilidade quando armazenadas sob temperaturas baixas (Hellmann et al 2006) sem, contudo, apresentarem teores de ROs compatíveis aos elevados níveis de sacarose encontrados nas sementes como um todo (Garcia et al 2006).…”
Section: Sementes Maduras De Caesalpinia Echinataunclassified
“…Initially, the lifespan of those seeds was considered short, tolerating no more than three months in natural storage ( Barbedo et al 2002). Later, important advances were obtained with the application of suitable techniques, such as the harvest at the physiological maturity point (Borges et al 2005), the control of drying (MartiniNeto & Barbedo 2015) and the storage, including the freezing (Hellmann et al 2006), fungus control (Lisbôa- Padulla et al 2009, Padulla et al 2010 and monitoring the chemical composition changes (Garcia et al 2006, Borges et al 2006, Hellmann et al 2008, Mello et al 2011, extending storage for up to five years (Mello et al 2013). However, this storage period is not enough to allow its inclusion in germplasm banks.…”
Section: Resultsmentioning
confidence: 99%